Complex I deficiency and Leigh syndrome through the eyes of a clinician. Issue 11 (30th October 2020) - Reinson, Karit; Õunap, Katrin
Abstract : Mitochondrial complex I deficiency is associated with a wide range of clinical presentations, including Leigh syndrome. Its genetic causes are heterogeneous, with poor genotype–phenotype correlation. It is impossible to identify the genetic defect of complex I deficiency using clinical observation and metabolic/imaging studies alone. As a result, whole‐exome sequencing (WES) is increasingly used in clinical work to identify an underlying genetic defect causing the disease. The article in this issue of EMBO Molecular Medicine by Alahmad et al (2020) is timely and valuable, as it expands on the genotype of mitochondrial complex I deficiency by identifying and characterising pathogenic variants of the NDUFC2 gene in children with Leigh syndrome. Abstract : K. Õunap and K. Reinson discuss the biochemical and functional characterization of the NDUFC2 pathogenic variants identified in children with Leigh syndrome by R. Taylor and colleagues, in this issue of EMBO Molecular Medicine